Telework as a form of limiting human and social capital depreciation among parents with young children - Kalinowska-Sufinowicz, Baha (Managerial Economics, 2016)
The main goal of the article is to present telework as a form of employment for parents with young children and its evaluation in the context of methods counteracting the depreciation of human and social capital – both from the labour demand and labour supply perspectives. The paper consists of two parts: a theoretical perspective and a practical one. The first part of the paper begins with a reflection on the phenomena of the depreciation of human and social capital in the light of literature review, especially with reference to the situation of parents raising young children. In the following – more practical – section, the concept and types of telework are introduced as well as its advantages and disadvantages from the points of view of employers and employees.